Respuesta :

Answer:

[tex]g(x) = (x - 2)^2 + 1[/tex]

Step-by-step explanation:

Given

[tex]f(x) = x^2[/tex]

Required

Determine g(x)

f(x) represents the parent function. And from the graph, we have:

[tex]f(x) = x^2[/tex]

f(x) is first shifted 2 units right.

The rule is:

[tex]f'(x) = f(x - 2)[/tex]

So, we have:

[tex]f'(x) = (x - 2)^2[/tex]

Next, f'(x) is shifted 1 unit up to give g(x), the blue graph.

The rule to this is:

[tex]g(x) = f'(x) + 1[/tex]

[tex]g(x) = (x - 2)^2 + 1[/tex]

Ver imagen MrRoyal